2017
DOI: 10.1021/acs.jpcc.7b08448
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Interfacial Charge Recombination for Boosting Power Conversion Efficiency in CdSe{Au} Nanohybrid Sensitized Solar Cell

Abstract: To boost the power conversion efficiency (PCE) of quantum dot solar cell (QDSC) by long-lived charge separated state, we are introducing CdSe{Au} nanohybrid material (NHM) which acts as a better light harvester than CdSe quantum dot (QD) alone. Steady state absorption studies show broadening of the absorption band of CdSe{Au} NHM up to 800 nm. The steady state and time-resolved luminescence studies reveal ultrafast electron transfer from CdSe QD to Au nanoparticles (NPs), forming a charge separated state. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 67 publications
(130 reference statements)
1
29
0
Order By: Relevance
“…In our continuous effort to correlate carrier dynamics with PCE we have employed TA spectroscopy to monitor the carrier relaxation and recombination dynamics in ultrafast time scale for several nanocrystal systems such as CdSeS, CdZnSSe alloy structures, CdSe/CdS core/shell structures and AuÀ CdSe heterostructures. [28,29,31,39,60,61] We have demonstrated how the charge carrier dynamics of intrinsic NC as well as at the NC/electrode interface gets affected by structural variation within the NC. Our conclusion was alloy NCs are superior candidates for QDSC due to their trap free nature and possibility of slower electron cooling.…”
Section: Resultssupporting
confidence: 54%
“…In our continuous effort to correlate carrier dynamics with PCE we have employed TA spectroscopy to monitor the carrier relaxation and recombination dynamics in ultrafast time scale for several nanocrystal systems such as CdSeS, CdZnSSe alloy structures, CdSe/CdS core/shell structures and AuÀ CdSe heterostructures. [28,29,31,39,60,61] We have demonstrated how the charge carrier dynamics of intrinsic NC as well as at the NC/electrode interface gets affected by structural variation within the NC. Our conclusion was alloy NCs are superior candidates for QDSC due to their trap free nature and possibility of slower electron cooling.…”
Section: Resultssupporting
confidence: 54%
“…The performance of polycrystalline PV cells can be significantly influenced by charge carrier dynamics and grain boundary engineering, hence their deep understanding in Cu-based quaternary chalcogenides will assist future optimization of PV devices to achieve improved performance. In earlier investigations, we have reported a direct correlation between efficiency and carrier dynamics in solar cells. Solar device performance can be significantly enhanced with elongated charge-carrier lifetimes when the grain size is increased from a few hundred nanometers to the micrometer level .…”
Section: Introductionmentioning
confidence: 83%
“…Meanwhile, metal−semiconductor nanohybrid materials (NHMs) were also used in enhancing light harvesting capability and photovoltaic performance of the resulting cells by Ghosh and coworkers. 328 Experimental results showed that the absorption onset of CdSe/Au can be red-shifted to 800 nm. Higher recombination resistance and longer electron lifetime were also confirmed by EIS measurements at TiO2−CdSe/Au interface in comparison with TiO2−CdSe.…”
Section: Alloyed Qdsmentioning
confidence: 99%